Mechanism of Coal Seam Permeability Enhancement and Gas Outburst Prevention under Hydraulic Fracturing Technology. (22nd March 2022) - Wu, Xinhua; Zhu, Tao; Liu, Yufei; Zhang, Guoyu; Zheng, Guanghui; Wang, Fengnian
Abstract : In view of the high gas pressure and low permeability of deep coal seam, it is difficult to control gas, which affects the safety production of coal mine. The technical scheme of hydraulic fracturing to improve the permeability of coal seam is put forward, and the gas drainage technology is used to control the gas emission of coal seam. The fracturing effect under different water pressure, different gradient fracturing times, and in situ stress is analyzed by using 3DEC (3-Dimensional Distinct Element Code) discrete element software. The simulation analysis and field verification results show that the coal seam gas pressure increases linearly with the buried depth. In situ stress characteristics and hydraulic strength are the key factors affecting the effect of hydraulic fracturing. The fracturing radius increases with the increase of flow. When the construction pressure of hydraulic fracturing test is 18 MPa, the distance between fracturing hole and drainage hole is 8.5 m. The actual measurement shows that after hydraulic fracturing and gas drainage, the maximum gas emission is reduced by 51%, and the average gas emission is reduced by 58%.